Enhancing Sustainability in Super-Intensive Shrimp Farming by Implementing a Closed Ecological System - Linh, Duong Mai; Kien, Tran Trung; Thao, Nguyen Thi Phuong; Thang, Nguyen Viet (Research on World Agricultural Economy, 2026)
This study aims to assess the sustainability of super-intensive shrimp farming using a sustainability indicators analysis that considers various factors. The indicators were selected based on the current state of super-intensive shrimp farming activities and observations of specific natural conditions in the study area. The study identified 18 indicators across three dimensions for assessing the sustainability of shrimp farming, including economic, environmental, and social. Furthermore, the study proposed and successfully implemented a closed ecological system to improve sustainability in super-intensive shrimp farming. The waste from the shiphong water exchange process includes shrimp shells, shrimp feces, and residual pond waste. Shrimp shells or carcasses are collected for composting. The final organic fertilizer is used for orchard cultivation and as a replacement for chemical fertilizers. The treated water is recirculated to a primary settling pond for further treatment before being returned to the super-intensive shrimp farming ponds. The results show that the implementation of the closed super-intensive farming system, which emphasizes material and energy recycling along with increased farming density, resulted in a total gross outcome index (GO) of $925,717.23. This figure is 11.2 times higher than that of the traditional super-intensive farming system. However, intermediate costs (IC) increased by $723,113.68. The closed system operates on an area of 0.09 ha/kg of shrimp, uses 0.15 m3 of water, and needs 1.01 MJ of energy. Additionally, the Nitrogen to Phosphorus (N:P) ratio is 0.27:0.05, and the use efficiency of N and P reach 87% and 81%, respectively. ER